2022
DOI: 10.4251/wjgo.v14.i6.1162
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological differences, risk factors and prognostic scores for western patients with intestinal and diffuse-type gastric cancer

Abstract: BACKGROUND In the molecular era, the Laurén system is still a cost-effective and widely implemented classification for gastric cancer (GC) and it has been recently associated with clinical, histological and molecular features of these tumors. Despite recent advances in the understanding of the molecular biology of GC, there is a need to develop new prognostic tools for patient stratification in clinical practice. Thus, the identification of easily available prognostic factors in patients with inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…According to the Laurén classification, described in 1965 and still used in clinical practice, GC can be divided into intestinal, diffuse, and mixed types[ 127 ]. As observed by our research team in a previous study, supporting findings from other investigators, there are differences in clinical, molecular, and prognostic characteristics between intestinal and diffuse GC[ 128 ]. Therefore, studying Laurén subtypes separately could enhance patient stratification both in clinical practice and in clinical trials.…”
Section: Gastric Cancersupporting
confidence: 90%
“…According to the Laurén classification, described in 1965 and still used in clinical practice, GC can be divided into intestinal, diffuse, and mixed types[ 127 ]. As observed by our research team in a previous study, supporting findings from other investigators, there are differences in clinical, molecular, and prognostic characteristics between intestinal and diffuse GC[ 128 ]. Therefore, studying Laurén subtypes separately could enhance patient stratification both in clinical practice and in clinical trials.…”
Section: Gastric Cancersupporting
confidence: 90%
“…Nonetheless, the poorer prognosis presented for EBV-positive patients found in our investigation may perhaps be explained by the fact that, in this sample, there were 27 tumors of the diffuse type against only 10 of the intestinal type and one with both. In the literature, it has been reported that diffuse tumors have a worse prognosis than intestinal ones 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Malanchi et al (2011) found that cancer stem cells expressing THY1 respond to increased matrix components at metastatic sites [71]. Moreover, Díaz Del Arco et al (2022) showed that desmoplasia, a fibrotic process resulting from accumulation of extracellular matrix components, is associated with intestinal gastric cancer when compared to the diffuse type [72]. The Thy-1 protein, encoded by the THY1 gene, is involved in mechano-signaling, a pathway that results from interaction with matrix components [73,74].…”
Section: Discussionmentioning
confidence: 99%